KARAKTERISTIK FISIKOKIMIA PATI AREN ASETAT YANG DIPRODUKSI PADA BERBAGAI JUMLAH PATI - yunita, Haerina; Rahim, Abdul; Rahmatu, Rostiati Dg (AGROTEKBIS, 2018)
The research objective was to determine the physicochemical characteristics of acetylated arenga starches produced in varying amounts of starch. Modification of arenga starch with treatment of starch at 50, 200, 350, 500, 650, 800 and 950 g by adding distilled water as much as 112.5; 450; 787.5; 1.125; 1,462; 1,800 and 2,137 mL respectively, stirred using a magnetic stirrer for 60 minutes. Then added acetic anhydride 15%(v/w) at pH 8 were added 3% NaOH solution. Then added a solution of 0.5 M HCl to pH 4.5 to stop the reaction.Further starch precipitated and washed with distilled water two to three times and one time 75% ethanol, starch and then oven-dried at 50 ° C for 12 hours. Variable research of acetylated arenga starches include acetyl percent and a degree of substitution (DS), water holding capacity and oil holding capacity (WHC and OHC), swelling power and solubility, emulsion stability and viscosity. Results of research on acetyl percent (4.28%) and the degree of substitution (0.17). Physicochemical characteristics of acetylated arenga starches WHC (1.71 g / g), swelling power (36.40 g / g), solubility (1.32%) and emulsion stability (100.00%) higher than the native arenga starch while OHC (2.05 g/g) and viscosity (2933 Cp) with native starch is higher than the acetylated arenga starches. Then, on the characteristics of acetylated arenga starches can be applied to the food product as a functional food.